Pengaruh Flash Sale, Kemudahan, dan Customer Review Terhadap Keputusan Pembelian Produk Pada Platform Marketplace - Hilmi Dzaki; Robiah, Siti; Drajat Stiawan (BISMA : Business and Management Journal, 2023)
The relationship between seller and buyer previously had limitations, mainly by distance and time. However, as more and more people use the internet, it opens up great opportunities for businesses who can take advantage of this digital marketing trend. Digital advancements provide an opportunity for them to advertise their goods through online marketplaces and be able to generate income for life. The purpose of this study is to analyze the effect of flash sales, convenience and customer reviews on product purchasing decisions on the marketplace platform. The research instrument uses data from the results of a questionnaire using a quantitative approach. Classical assumption test analysis, multiple linear regression analysis, and analysis of the coefficient of determination were all used in analyzing the data. Data analysis used SPSS software version 25. The findings of the study show that flash sales, convenience and customer reviews all have an impact on consumer decisions to buy products on the marketplace platform. These three variables have the power to influence 81.8% of the decision making process when buying a product.